As economias do tempo em tempos de economia: um Brasil nas publicidades da Revista Veja (1974-1994) - Chagas, Beneângelo Soares (2021)
In the vast area of Clio, the image supports have not been new for a long time. With the rise of Cultural History in the 1970s, the already existing debates around the role of images as historical sources gained intensity and won the interest of many researchers, to be noticed by the expressive amount of productions that put the images at the heart of their discussions, in which photographs, cinema, paintings, television and advertisements, among others, were used. Taking as a source of research a type of the latter, the advertisements, those carried by weekly magazine Veja between 1974 and 1994, the present work as developed. This period was marked, in many countries in Latin America, Africa and western Asia, as a time of strong inflationary crises and marked economic recessions. Between the “Oil Crisis” and the Real Plan, in those years, in Brazil, a whole cycle of (uneven) economic growth ended and the propagandized “Brazilian Miracle” came to an end. In these decades, the national economy slowed, entered a recession and social inequality in the country worsened even more. Con-comitant to this, as with other cultural forms, Brazilian advertising – production and field – was censored. Less paradox than force play, it also went through its phase of greatest growth in the world advertising scene. As the advertising expression is marked by an optimistic dis-course, which finds in times of economic prosperity more opportunities to interact socially, the research seeks to understand how, in a period of crisis, advertising translated time, con-flicts, anxieties and expectations of everyday life. For, if too dependent on the social structure and very sensitive to its changes, how did advertising interact with the crisis that Brazil was going through? And how did the relationship between the announcement of the crisis and the advertisements of times of crisis happen, in the disputed space of Veja – which became the magazine with the greatest circulation in the country and also the one with the greatest adver-tising load –, the relation between announce the crisis and the announcements the times of crisis? What about censorship? These are, among others, the questions that guide the investi-gation. The methodology used consisted of both the interpretation of the advertisements in their time, as well as their interaction with other sources of research, such as the magazine Propaganda and the Yearbooks Creation Club of São Paulo, indicators of the national adver-tising modus faciendi. We think that the Brazilian advertising rhetoric of the period in ques-tion was built mainly under the “concepts” of economy, technology, distinction and future. However, based on advertising as a remnant and indication of time, what does this mean and what else is it possible to say about Brazil in those years?